(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Long-term smoking is thought to cause vagal stimulation. The increase in suppressor cells associated with smoking predetermines the disruption of immune surveillance of tumor cell growth and the development of cancer. A significant correlation has been established between the level of morbidity and mortality due to cancer and the amount of tobacco consumed. When determining the nonspecific resistance of the body, it was revealed that tobacco smoke suppresses the phagocytic and degradation functions of the liver and spleen, inhibits the release of lysosomal enzymes and the production of superoxide. Treatment of fresh blood serum with cigarette smoke sharply reduces its bactericidal properties, but the simultaneous use of an antioxidant prevents this effect. In smokers, compared to non-smokers, serum IgE levels are significantly increased. In the blood of the umbilical cord of babies born to smoking mothers, the content of IgE is increased, and in the children themselves, the risk of various symptoms of atony is increased by 4 times.